Enhancing Early Childhood Language Skills through Audio-Visual Storytelling: A Pre-Experimental Study - Zulkifli Surahmat; Rahmaniar Rahmaniar; Emelia Fitri Limchio Sinaga (Universitas Muhammadiyah Barru, 2026)
This study investigates the effectiveness of storytelling supported by audio-visual media in improving early childhood language skills at an Islamic kindergarten in Maritengngae District, Sidenreng Rappang Regency. The research employed a pre-experimental design using a one-group pretest–posttest approach. The participants consisted of early childhood learners whose language abilities were assessed before and after the implementation of storytelling activities using audio-visual materials. Data were collected through structured observation sheets covering four language domains: listening, speaking, reading, and writing, and were analyzed descriptively using percentage-based achievement indicators. The findings reveal a substantial improvement in children’s language skills across all assessed domains. Children’s listening abilities improved through better comprehension of instructions and repetition of complex sentences, while speaking skills developed through answering questions, narrating cause-and-effect events, and naming objects. Reading skills increased as children became more proficient in recognizing letters, symbols, and words, and writing skills improved through name writing and meaningful drawing activities. Overall, children’s language performance increased from approximately 50% in the pretest to 85% in the posttest, indicating that classical learning completeness was achieved. The results suggest that storytelling with audio-visual media creates an engaging and supportive learning environment that enhances children’s motivation and active participation. This study concludes that audio-visual storytelling is an effective and innovative instructional approach for fostering comprehensive language development in early childhood education.